The Potential For Structural Modification Hence Benefit In Osteoarthritis Of Knee By Mineral Supplementation - Pilot Study - DR HIMANSHU BANSAL,; DR ANUPAMA BANSAL, (International Journal of Pharma and Bio Sciences, 2012)
The potential for structural modification by natural mineral supplement was evaluated in a pilot perspective, study of six months duration in twenty patients with moderate Osteoarthritis of knee. WOMAC values (subsets and total) showed significant improvement from baseline over the course of six months treatment (p < 0.001). The pain free distance covered during a Six minute walk (6MWD) also significantly improved by 140 feet ((p<.001). Requirement of rescue medication decreased to once a week in 45%. The mean (SD) change for the percentage of painful days was 45.0 (38.7). 25% patients demonstrated improved cartilage thickness by at least 0.01 mm as against 15% who lost thickness at least by 0.01 mm. 55% patients showed improved Cell counts (below 500 microlitre) in Synovial fluid. Hematological and Biochemical safety variables showed that mineral supplement is absolutely safe. The study suggests that natural mineral supplementation helped in synovial metabolism and in reducing cartilage pathology hence had structural efficacy.